Соціально-філософський аналіз трансформації антропологічного фактора у контексті сучасного економічного розвитку - Остапенко, І.Г. (Культура народов Причерноморья, 2014)
У статті проводиться соціально-філософський аналіз ролі антропологічного фактора у економічному розвитку сучасного суспільства. Економічні закономірності розглядаються в контексті соціальних тенденцій, відповідно до яких від членів суспільства за певних умов очікується певний образ дій. Зазначається, що науково - технічний прогрес, будучи причиною поліпшення матеріальних умов життя, одночасно зробив можливим цілий ряд найважливіших процесів соціальної модернізації, що в свою чергу призвело до зміни ролі антропологічного фактора в глобальній економіці. В статье проводится социально - философский анализ роли антропологического фактора в экономическом развитии современного общества. Экономические закономерности рассматриваются в контексте социальных тенденций, согласно которым от членов общества при определенных условиях ожидается определенный образ действий. Отмечается, что научно - технический прогресс, являясь причиной улучшения материальных условий жизни, одновременно сделал возможным целый ряд важнейших процессов социальной модернизации, что в свою очередь привело к изменению роли антропологического фактора в глобальной экономике. The article socio -philosophical analysis of the role of anthropological factor in the economic development of modern society. In the context of modern industrial society, according to a retrospective analysis of its economic development, it may be noted that the capitalist mode of production and the market economy as a favorable environment for its development, given unprecedented in the economic history of Europe result.. At the end of the twentieth century. level of development and sophistication of the productive forces reached its highest level, which directly affected the material well-being and living standards of people in today's society. In addition, the industrial revolution are not limited to only the technological aspects. This change was the cause of fundamental economic transformation. The object of the article: economic reality as an area of socio- humanities. Objective: To determine the dynamics of the anthropological factor in the economic development of modern society. Economic laws are discussed in the context of social trends, according to which members of the public in certain circumstances a certain course of action is expected. It is noted that the scientific - technical progress, causing improvement in the material conditions of life, at the same time made possible a number of important processes of social modernization, which in turn led to a change in the role of anthropological factor in the global economy.